Tolerance and Biological Activity of Pentosan Polysulfate After Intramuscular or Subcutaneous Administration for Ten Days in Human Volunteers - Sié, P; Albarede, J L; Robert, M; Bouloux, C; Lansen, J; Chigot, C; Correll, S; Thouvenot, J P; Boneu, B (Thrombosis and Haemostasis, 1986)
This study reports on the tolerance and the pharmacological activity of pentosan polysulfate (PPS) administered to healthy volunteers for 10 days. Three groups of 10 subjects received either one daily injections of 100 mg of PPS by I. M. route (group I), or two daily injection of 50 mg of PPS by I. M. or S. C. route (groups II and III, respectively). In each group two random subjects received a placebo for the 10 days; on day 0, each subject was injected by a placebo. Clinical tolerance was checked by a daily physical examination; biological tolerance was assessed comparing the results of the main biochemical and haematological constants measured before starting the treatment (day 0) and 12 or 24 h after the end of the treatment (day 11). The pharmacological activity was measured on serial samples taken before treatment and between 1 and 6 h after the drug injection on days 1, 3 and 10; the results were compared to those obtained on day 0. Clinical tolerance was good. The biological side effects concern the transaminase levels and the platelet counts. An increase above the upper normal limit was observed in 18/i4 and 3/24 for alanine and aspartic transaminase respectively. The mean platelet reduction ranged between 24 and 34% according to the groups. The drug injection induced a slight Quick time (PT) prolongation, no significant alteration of factors II, VII-X, V levels and of thrombin clotting time. The activated partial thromboplastin time (APTT) was significantly prolonged and there was a weak but significant circulating anti-Xa activity. The fibrinolytic activity was enhanced without increase in the tissue plasminogen activator antigen level. These pharmacological effects were at their maximum between 2 and 4 h after the drug injection and returned to the pre-injection equilibrium between 4 and 6 h except for circulating anti-Xa activity; these effects remained unchanged all over the 10-day therapeutic period. The comparison between group I and II indicates that the PT and APTT effects are dose-dependent while the anti-Xa and the profibrinolytic effects are not; the comparison between group II and III indicates that the S. C. and I. M. route are bioequivalent.
Keywords: Heparinoid; Pentosan polysulfate; Hemoclar